A trading and pricing method of expansion options for BOT freeway projects in China. Issue 7 (29th May 2019) - Sun, Hui; Wang, Yuning; Meng, Jia
Abstract : Purpose: The purpose of this paper is to develop a trading and pricing method of expansion option (EO) model to solve expansion problems of build-operate-transfer (BOT) freeway project. Design/methodology/approach: This paper proposes an ex ante mechanism through trading the EO to avoid the transaction costs. By editing the paths generated from binomial option pricing model, this paper establishes an American real option binomial lattice model and evaluates the value of EO. Data are collected from Liaoning province in China and the model is practiced in the context of a BOT freeway in Liaoning province. Findings: Supported by empirical evidence, this study finds out that there exists a minimum price at which the government can sell the EO and a maximum price that the private sector is willing to pay. When the minimum price is negative, the government should transfer the EO to the private sector free of charge to avoid the transaction costs. Otherwise, the government should sell the EO at a reasonable price to protect public interests. Practical implications: The study can be used for the government to reducing the transaction costs. By using the trading EO model, the government can sell its share of the EO to the private sector to manage its resources efficiently. Originality/value: This paper builds a trading EO model to solve expansion problems instead of renegotiations. In addition to reducing the transaction costs for the whole society, trading EO can also raise the respective payoffs of both public and private sectors. An EO trading framework and algorithm is further developed. It realized an American option model, making the owner can exercise the option whenever he wants. Thus, the whole model is adapted to best fit BOT highway practice.